Therapeutic Communities: the construction of an asylum and prohibitionist policy - Prudencio, Juliana Desiderio Lobo; Theodoro , Laís Santos; Baqueiro, Victoria Lavignia de Oliveira (Argumentum, 2023)
This article presents a study on the National Policy on Mental Health, Alcohol and Other Drugs, showing how Brazilian Therapeutic Communities (TCs) form part of the care provided to drug users in Brazil. This is a documentary analysis of regulations, based on a bibliographical review. We observed that the TCs gained strength in a variety of political, social and economic scenarios, especially after 2015, and became the main institutions for the care of drug users financed by the public purse. We further note that TCs represent a call to the logic of the asylum. They are prohibitionist, and detain drug users, mostly men, black, and poor, under the logic of abstinence, forced labour, religiosity and discipline.